The role of basigin in reproduction. Issue 2 (February 2020) - Li, Kailiang; Nowak, Romana A
Abstract : Basigin is a highly glycosylated transmembrane protein that was originally identified as a product of tumor cells. Basigin is a potent inducer of matrix metalloproteinases (MMPs) and angiogenic factors such as vascular endothelial growth factor (VEGF). Basigin is also a chaperone protein for specific metabolite transporters in the plasma cell membrane such as the monocarboxylate transporters and is an important regulator of cell metabolism. Studies in reproductive model systems have demonstrated that basigin is expressed in the testis, ovary, uterus and placenta and is necessary for normal fertility in both males and females. Overexpression of basigin is associated with reproductive diseases including uterine leiomyomas and endometriosis. This review presents an overview of the literature regarding the physiological role of basigin in reproductive tissues and the mechanistic pathways involved in its actions.